2017
DOI: 10.1038/s41598-017-09985-6
|View full text |Cite
|
Sign up to set email alerts
|

Strong electric wave response derived from the hybrid of lotus roots-like composites with tunable permittivity

Abstract: Lotus roots-like NiO/NiCo2O4 hybrids derived from Metal-organic frameworks (MOFs) are fabricated for the first time by using flake NiCo-MOF precursors as reactant templates. It was found that a thin sample consisting of 60 wt % NiO/NiCo2O4 hybrids in the wax matrix exhibited an effective microwave absorption bandwidth of 4.2 GHz at the thickness of 1.6 mm. The highest reflection loss of −47 dB was observed at 13.4 GHz for a sample with a thickness of 1.7 mm. Results obtained in this study indicate that hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…If the thickness of absorber ( t m ) at peak frequency ( f m ) meets the formula where c represents the velocity of light in the free space, and |μ r | and |ε r | are the moduli of μ r and ε r . To demonstrate the maximum RL value appearing at 2.4 mm, as shown in Figure , we conduct the simulations of absorber t m at the minimum RL values versus peak frequency ( f m ) for S2 under λ/4 conditions . The black curve is on behalf of the simulation thickness ( t fit m ) at 2–18 GHz via violet dots, and quarter wavelength principles are the experimental matching thickness ( t exp m ) at f m .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the thickness of absorber ( t m ) at peak frequency ( f m ) meets the formula where c represents the velocity of light in the free space, and |μ r | and |ε r | are the moduli of μ r and ε r . To demonstrate the maximum RL value appearing at 2.4 mm, as shown in Figure , we conduct the simulations of absorber t m at the minimum RL values versus peak frequency ( f m ) for S2 under λ/4 conditions . The black curve is on behalf of the simulation thickness ( t fit m ) at 2–18 GHz via violet dots, and quarter wavelength principles are the experimental matching thickness ( t exp m ) at f m .…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the maximum RL value appearing at 2.4 mm, as shown in Figure 12, we conduct the simulations of absorber t m at the minimum RL values versus peak frequency (f m ) for S2 under λ/4 conditions. 41 The black curve is on behalf of the simulation thickness (t fit m ) at 2−18 GHz via violet dots, and quarter wavelength principles are the experimental matching thickness (t exp m ) at f m . We found that the value of t exp m at 2.4 mm fits well with the simulation t fit m , whereas the t exp m deviates from t fit m to variable extents.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The values of both ε′ and ε′′ of MDCF dropped sharply with increasing frequency, while those of SiC/MDCF and SiC/MDCF–Aerogel remained roughly balanced with the fluctuation phenomenon at high frequency in Figure a and b. On the basis of the Debye theory, ε′ and ε′′ were calculated as eqs and where ω is the angular frequency, τ is the polarization relaxation time, and σ ac is the alternative conductivity. ε ∞ is the high-frequency limit relative dielectric permittivity, ε s is the static permittivity, and ε 0 is the dielectric constant in vacuum.…”
Section: Resultsmentioning
confidence: 99%
“…By combining the profiling data of the MDCF–wax composite, we find that as to the SiC/MDCF–Aerogel–wax composite, the impedance matching ratio played a crucial role in achieving the lowest reflection loss value. When the impedance matching ratio reached a particular value, the attenuation loss began to have an impact. , …”
Section: Resultsmentioning
confidence: 99%
“…Their results demonstrated that the sample exhibited a maximum RL value of − 28.6 dB at 14.96 GHz. Porous NiO/NiCo 2 O 4 lotus root-like nanoflakes were demonstrated by Liang and co-workers as a promising candidate for a microwave absorbent [29]. The NiO/NiCo 2 O 4 (60 wt%)-wax hybrid showed the strongest EMW absorption with the RL value of − 47 dB at 13.4 GHz.…”
Section: Introductionmentioning
confidence: 99%